Digital technology overuse as a predictor of digital amnesia and productivity - Chiew, Ooi Yan; Lai, An Qi; Liew, Wen Xin (2020)
Currents Malaysian young adults are the most prominent group for the future of developing individual contribution to society. They are the most interactive group on using digital technology. In this case, we found that there is more remarkable digital technology overuse. The present study is required to examine the relationship between digital technology overuse and digital amnesia and productivity. Moreover, also a study about whether digital technology overuse does significantly predict digital amnesia. On the other hand, the current study also sought whether digital technology overuse significantly predicted low productivity. Overall, the present study is mainly targeted at young adults in Malaysia. The instruments included in this research study are Digital Addiction Scale (DAS), Everyday Memory Questionnaire-Revised (EMQ-R) and Work Productivity and Activity Impairment: Specific Health Problem (WPAI-SHP). In this study, 121 participants were required to use convenience sampling through an online survey spread across various social media platforms. The data collection will be applied on Qualtrics online platform. Besides, the proposed statistical analysis is Simple linear regression. The results found that it is significant between digital technology overuse and digital amnesia. However, digital technology overuse is not significant with productivity. Furthermore, the results revealed that digital technology overuse is negatively significantly predicted digital amnesia. Nonetheless, there is no significant predicted low in productivity when digital technology overuse. Theoretically, the present research has committed to the latest results of the past literature, especially on Malaysian young adults. Hence, it was looked upon as limited. Besides, the practical contribution of the present finding should be beneficial in mental health and non-governmental parties. Thus, it enables them to devise related activities and modules to assist young adults in Malaysia who face excessive use of digital technology.